2019
DOI: 10.1530/ec-19-0247
|View full text |Cite
|
Sign up to set email alerts
|

The neuropeptide 26RFa in the human gut and pancreas: potential involvement in glucose homeostasis

Abstract: Objective Recent studies performed in mice revealed that the neuropeptide 26RFa regulates glucose homeostasis by acting as an incretin and by increasing insulin sensitivity. However, in humans, an association between 26RFa and the regulation of glucose homeostasis is poorly documented. In this study, we have thus investigated in detail the distribution of 26RFa and its receptor, GPR103, in the gut and the pancreas, and determined the response of this peptidergic system to an oral glucose challenge in obese pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 37 publications
5
27
0
Order By: Relevance
“…More recently, the implication of the 26RFa/GPR103 neuropeptidergic system in the control of glucose homeostasis was reported. We, and others, found that 26RFa and GPR103 are strongly expressed by β cells of the pancreatic islets (24,25,27), and that the neuropeptide prevents cell death and apoptosis of β cells (27). We also showed that 26RFa is abundantly expressed all along the gut and that i.p.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…More recently, the implication of the 26RFa/GPR103 neuropeptidergic system in the control of glucose homeostasis was reported. We, and others, found that 26RFa and GPR103 are strongly expressed by β cells of the pancreatic islets (24,25,27), and that the neuropeptide prevents cell death and apoptosis of β cells (27). We also showed that 26RFa is abundantly expressed all along the gut and that i.p.…”
Section: Introductionmentioning
confidence: 74%
“…Accumulated data obtained during the last decade have promoted the evidence that the neuropeptide 26RFa plays a key role in the control of feeding behaviour (10, 13, 14) and the regulation of glucose homeostasis (24, 25, 27, 28). Supporting this notion, it has been recently shown that acute administration of a GPR103 (the 26RFa receptor) antagonist decreases food intake (30) and reduces the global glucose-induced incretin effect as well as the insulin sensitivity (28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations